Acordo de pesca como instrumento de gestão participativa na Amazônia - Cerdeira, Regina Glória Pinheiro (2009)
This research approaches the fishing agreements as an instrument of fishery participatory management developed in the Amazon. It describes the environment of várzea as the scenario of relationships that are established as from the use of a resource of public access like fish; and as the main areas of fishery in inner waters of the Amazon. The fishery community-based agreements, developed from pressures over environments of lakes of ribeirinhos communities are the main instrument of participatory fishery management and they have been presented as a promising way to control conflicts, reduce over fishing and increase fishing productivity in the lakes. However, the research also focuses on the need of monitoring and evaluating this instrument in order to have consolidated results in the purpose of management. One of the challenges of this community-based co-management is to guarantee the public access and the appropriate management of fishing resource before the antagonistic interests of users over the resource. It approaches, yet, under a legal analysis, the only legal document, the normative instruction IBAMA n. 29/02, which determines in specific forms, clear criteria for the creation of these agreements, aiming to generate complementary rules to fishing laws; besides the new concepts of fishing determined by the Law n.11.959/2009. The analysis of fishing agreements is done, also considering the participatory management that has been developed in the region of Urubu River, in the town of Boa Vista do Ramos/AM, taking into account socioeconomic aspects of the communities and the impressions of the inhabitants about the validity and efficacy of the rules in the Portaria IBAMA N. 11/2003. In this study, it’s discussed that the participation of users in natural resources management, like fish, is fundamental, but before organizational structures strengthened with the ability of mobilization, coordination and representation of the group, with leaders who are able to act as interlocutors in the processes of co-management. In this aspect, the communities in the region of Urubu River in Boa Vista do Ramos still need development. The lack of articulation between this communities and involvement with the local fishing organization can be pointed as important reasons for the decadence observed in the valid fishing management; however this agreement has also presented positive aspects like the control of conflicts around the fishing activities and the feeling of abundant fish, even in its beginning.